Meningkatkan Keterampilan Berbicara Mahasiswa Pendidikan Bahasa Arab STAIN Bengkalis Melalui Strategi Langsung Rebecca L. Oxford - Sariyati Sariyati (STAIN Bengkalis, 2021)
This research aims to determine the improvement of speaking skill among students of Arabic Language Education at Sekolah Tinggi Agama Islam Negeri Bengkalis through direct strategies by Rebecca L. Oxford. This is a descriptive qualitative research where the observation and documentation are applied to collect the data from 16 respondents. These respondents are selected through the total sampling technique from the students of Arabic Language Education at Sekolah Tinggi Agama Islam Negeri Bengkalis for 2019/2020 academic year. The result of this research shows the improvement of speaking skill among students of Arabic Language Education at Sekolah Tinggi Agama Islam Negeri Bengkalis is very significant. In addition, direct strategies by Rebecca L. Oxford are effective in improving students speaking skill.